Determining feed budgets for farm-specific nutritional programs - Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Use of feed budgets simplifies feed delivery and improves the accuracy of delivering diets to the correct pig weight ranges during the nursery and finishing periods. Little information has been available for determining farm-specific feed budgets in the past. In this paper, we will outline simple methods to customize a feed budget for individual farms using feed efficiency from past closeout records.
Keywords: Swine; Feed budgets; Farm-specific nutritional programs